Did euro leaders say goodbye to the IMF? - Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2012)
This policy brief takes stock of the agreement by Eurozone countries in late June at the European summit. If this agreement survives (which is by no means certain) and is utilised, Eurozone governments will have opened the door to a flexible use of its bailout funds. In contrast to previous packages, such flexible use could involve direct recapitalisation of banks (bypassing sovereigns) or purchasing of government bonds in order to assist governments teetering on the edge of sovereign default. The primary concern of this paper, however, is that such use would be likely to close the door to cooperation between the Eurozone and the IMF in new rescue packages. (...)
Keywords: 330; Eurozone; IWF-Kredit; Entwicklungshilfekonditionen